Deletion of maternal UHRF1 severely reduces mouse oocyte quality and causes developmental defects in preimplantation embryos. Issue 7 (17th April 2019) - Cao, Yumeng; Li, Mingrui; Liu, Fei; Ni, Xiaobei; Wang, Shuai; Zhang, Hao; Sui, Xuesong; Huo, Ran
ABSTRACT: The ubiquitin‐like, containing PHD and RING finger domains, 1 (UHRF1) protein recognizes DNA methylation and histone modification and plays a critical role in epigenetic regulation. Recently, UHRF1 was shown to have a role in DNA methylation in oocytes and early embryos. Here, we reveal that maternal UHRF1 determines the quality of mouse oocytes. We generated oocyte‐specific Uhrf1 ‐knockout mice and found that females were sterile, and few maternal UHRF1‐null embryos developed into blastocysts. The UHRF1‐null oocytes had an increased incidence of aneuploidy and DNA damage. In addition to defective DNA methylation, histone modification was affected during oogenesis, with UHRF1‐null germinal vesicle and metaphase II‐stage oocytes exhibiting reduced global histone H3 lysine 9 dimethylation levels and elevated acetylation of histone H4 lysine 12. Taken together, our results suggest that UHRF1 plays an important role in determining oocyte quality and affects epigenetic regulation of oocyte maturation as a maternal protein, which is crucial for embryo developmental potential. Further exploration of the biologic function and underlying mechanisms of maternal UHRF1 will enhance our understanding of the maternal control of the oocyte and early embryonic development.—Cao, Y., Li, M., Liu, F., Ni, X., Wang, S., Zhang, H., Sui, X., Huo, R. Deletion of maternal UHRF1 severely reduces mouse oocyte quality and causes developmental defects in preimplantation embryos. FASEB J. 33, 8294–8305 (2019). www.fasebj.org